A Wideband Inductorless Programmable Gain Amplifier Using 90-nm CMOS for High-Speed Communication - Taufiq Alif Kurniawan; Tzu-Yu Lin; Chi-Tshao Wang; Hsiao-Chin Chen; Arief Udhiarto (IEEE Access, 2025)
This paper presents a wideband inductorless programmable gain amplifier (PGA) for high-speed communication. The proposed circuit employs a Cherry-Hooper amplifier structure as the gain cell and an active inductor, achieving a wide bandwidth with relatively low power consumption and a compact chip design. An in-depth analysis was conducted on the distinctive technique employed by this structure to achieve a wide bandwidth and precise gain control. A 6-bit control switch was utilized to attain the precise zero and self-resonant frequencies of the active inductor. The chip is fabricated using 90-nm CMOS technology, with a chip size of 0.3 mm2 and consuming 39.3 mW from a 1.2 V supply voltage. The on-chip measured results show a voltage gain ranging from 21 to 49 dB with a 4-dB step and a 2.1 GHz bandwidth. The gain step errors were within +0.1 dB to +0.7 dB. The inductorless topology achieves wideband performance and precise gain control, demonstrating the suitability of the proposed technique for high-speed communication PGA.